Influence of quantum phase transition on spin conductivity in the anisotropic three-dimensional ferromagnetic model. (January 2017) - Lima, L.S.
Abstract: We use the SU(3) Schwinger boson formalism to study the spin transport in the three-dimensional S =1 Heisenberg ferromagnet in the cubic lattice with an easy plane crystal field, considering first-, second- and third-neighbor interactions. We have got one single peak for the spin conductivity for this system at ω = ω k and a variation of the height of the peak with the parameters D c and η, and hence an influence of the quantum phase transition, between the disordered paramagnetic phase and the ordered ones, on the spin conductivity of this system. We have considered the exchange interaction J 1 as ferromagnetic and the interactions J 2 and J 3 as antiferromagnetic. Highlights: We got the spin current operator using the Schwinger boson formalism. We employed the Kubo formula and we got the spin conductivity for this model. We found a sudden variation oft he height of peak in the range where the parameter Dc falls to zero in the graphic Dc vs. h . Therefore we obtain an influence of the quantum phase transition on the spin transport.